Artesunate Restrains Maturation of Dendritic Cells and Ameliorates Heart Transplantation-Induced Acute Rejection in Mice through the PERK/ATF4/CHOP Signaling Pathway - Yuanyang Chen; Sihao Zheng; Zhiwei Wang; Xin Cai; Yanjia Che; Qi Wu; Shun Yuan; Xiaohan Zhong (Hindawi Limited, 2021)
Background. Heart transplantation (HT) is the only effective treatment for end-stage heart failure because it can effectively improve the survival rate and quality of life of patients with heart failure. Artesunate (ART) is an artemisinin derivative, with good water solubility and higher oral bioavailability. The main aim of this study was to determine the role of ART in HT mice. Methods. In animal experiments, mice were divided into the control group, HT group, low ART+HT group, and high ART+HT group. Next, inflammatory cell infiltration, oxidative stress injury, and myocardial cell apoptosis were determined in heart tissue. The proportion of multiple lymphocytes in spleen and lymph nodes was then determined using flow cytometry. In addition, cell experiments were conducted to determine the changes in expression of surface maturation markers of BMDC and changes in intracellular reactive oxygen species after LPS stimulation. Finally, western blot analysis was performed to determine the levels of endoplasmic reticulum stress-related proteins (CHOP/ATF4/PERK). Results. The survival time of mice in the ART treatment group was significantly prolonged and was positively correlated with the dose. In animal experiments, ART significantly reduced inflammatory cell infiltration in heart tissue and the proportion of CD4+CD8+ T cells in spleens and lymph nodes. Moreover, ART treatment lowered the 8-OHdg in hearts and myocardial apoptosis. In cell experiments, ART treatment slowed down the development and maturation of BMDCs by inhibiting the expression of endoplasmic reticulum stress-related proteins. Furthermore, the treatment alleviated the oxidative stress damage of BMDCs. Conclusion. ART can inhibit maturation of dendritic cells through the endoplasmic reticulum stress signaling pathway, thereby alleviating acute rejection in mice after heart transplantation.